Upon the treatment of respiratory affections: by the intra-tracheal injection of drugs - Talent, John William (The University of Edinburgh, 1899)
(1).. As the result of my observations on the above ten patients, I conclude that the most favourable cases for the intra-tracheal treatment, are those of early Phthisis and Tracheitis. Holt (8) and Marland (10) were such cases of early phthisis, and obtained marked benefit, in fact are both returned to their occupations in greatly improved health: the patient Holt improved remarkably in a few days, although he had had a cough for two years, and some loss of flesh for two months; the slight dulness in percussion over the apex, was however not cleared up by the treatment. Marland felt stronger, coughed less, began to eat well and sleep well, and showed a gain in weight,, also his sweating and diarrhoea were much lessened. These results may be taken as the usual effects of the intra-tracheal treatment, in suitable cases.

(2). In late Phthisis I found no real benefit at all e.g., Marshall (3) and Bowden (6). Both these were advanced cases. At first they seemed to think the {cough was a little easier after the injection, and that they slept better at night, but the improvement was to me, so doubtful, that after a few trials I gave it up

(3). Phthisis which is midway between early and date, is represented by Butler" (4): this case took the injections steadily and easily, and improved under them in the matter of cough, sleep and sweating though no alteration in the physical conditions or in the temperature was observed. The reason 'of the rise of temperature in the week 83rd to 30th, is doubtful: it might be due to the injection causing inoculation of a fresh portion of lung, a danger which is apprehended by some. The injections had been given daily for sixteen days before this occurred, after that week the temperature fell, but still remained persistently higher than before.

(4). Carroll (2) Suffering from Tracheitis, represents a class which appears likely to be very amenable to the treatment, since here the fluids are brought into direct contact with the inflamed surface in a way which seems' impossible for steamed or vapourised. medications. As a matter of fact, this |one case was better in two days.

(5). The cases I treated of Chronic Bronchitis |were practically not improved at all. This result |may be due to the fact that they were all three of very old standing, and associated with emphysema, since Dr. Thompson has got satisfactory results in Chronic Bronchitis. Godwin (1) Mitchell (5) Wilson (9) Godwin said that at first it eased his cough, warmed his body and helped him to expectorate more freely: the last injection he insisted, made him very ill,, but this may have been an attack of dyspnoea due to his emphysema, induced by some exertion. Wilson and Mitchell gained no benefit whatever.

As to cases of Acute Bronchitis I have had no experience, neither of Syphilis of the lung which Dr. Thompson says yields to this treatment, nor of Bronchietasis as recorded by Prof. Sir.T.Grainger Stewart

In most of the patients the injections were made without any difficulty, and without the use of the laryngoscope. The patient holding down his tongue, the tip of the syringe is passed downwards, behind the "base of the tongue, the patient told to inspire, and the injection delivered. After a few deep inspirations and a cough or two, there was usually no further trouble. In one or two the throat as so sensitive as to need spraying in preparation.

In McGovren's case, he was persistently sick on taking the first meal after the injection: since this was often in two hours' time it could hardly be from the fluid passing down the pharynx by mis¬ take.

As to the mixture injected, four different ones have been used in the above quoted cases, viz :- (a). Menthol 10$, Guiacol 2$, Olive Oil 88$. This is Sir. T.Grainger.Stewart's Solution, and is usually very soothing to"the cough and helps to sleep. (b). Menthol 2%, Guiacol 1%, Paroleine 97%. (c). Dr. Colin Campbell's mixture, made as follws :- (a). Benzosol 24 grains, rectified spirit 0.5 drachm: mix and add Price's Distilled Glycerine 0.5 ounce: dissolve by heat. (b). Menthol 24 grains, rectified spirit drachm, glycerine (as above) 0.5 ounce: dissolve by heat. Mix a and b and keep at a temperature of 90° Fahr. or warm before using. (d). Thymol 5%. Guiacol 2% Paroleine 93%. This combination, was used with good, effect. (e). Duotal 2% Menthol 10% Paroleine 88%. This I have had made up but have not yet used. Prof. Bayer of Brussels has lately used warmed creosotal in cases of tuberculosis and chronic bronchial catarrhs, injecting to 0.5 to 1.5 cub. cms. every second day.